2011
DOI: 10.5012/bkcs.2011.32.4.1143
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Modification of Novel Iminecalix[4]arene Derivatives

Abstract: The synthesis of novel iminecalix [4]arenes and further modification thereafter is described using a synthetic strategy. The reaction of the benzaldehyde derivatives with tetraamine functions on the calix[4]arene easily afforded the pure compounds in 92.4-95.7% yields, regardless of the effect of the substituents on the benzaldehyde derivatives. These compounds were stable under the conditions to obtain their analogue dialkylated in the narrow rim, with 83.2-89.9% yields. Characterization of the newly synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…[42][43][44][45] Based on the knowledge of the mixed-self assembled monolayer and the molecular recognition properties of the imincalix [4]arene 5, and aminocalix [4]arnes 6-9, recently, T. Kim et al introduced the phenomenon of molecular recognition to immobilize oligonucleotides on aminocalix [4]arene (AMCA) slides for the production of 9G DNAChips. 46 The preparation of the 9G DNAChip and the hybridization thereafter is briefly explained in Scheme 4.…”
Section: Chem Soc Revmentioning
confidence: 99%
“…[42][43][44][45] Based on the knowledge of the mixed-self assembled monolayer and the molecular recognition properties of the imincalix [4]arene 5, and aminocalix [4]arnes 6-9, recently, T. Kim et al introduced the phenomenon of molecular recognition to immobilize oligonucleotides on aminocalix [4]arene (AMCA) slides for the production of 9G DNAChips. 46 The preparation of the 9G DNAChip and the hybridization thereafter is briefly explained in Scheme 4.…”
Section: Chem Soc Revmentioning
confidence: 99%
“…The synergism between the calix [4]arene moiety and the para-azo substituent groups at the upper rim contributed significantly towards the antiradical and antioxidant activity. Iminecalix [4]arene derivatives are known to possess a deep cavity and hyperconjugation [53]. The water-soluble iminecalix [4]arene derivatives are reported for the molecular recognition of various organic molecules [54].…”
Section: Gorghiu Et Al Reported the Contribution Of P-t-butylcalixmentioning
confidence: 99%
“…Iminecalix [4]arene derivatives are known to possess a deep cavity and hyperconjugation [53]. The water-soluble iminecalix [4]arene derivatives are reported for the molecular recognition of various organic molecules [54].…”
Section: Gorghiu Et Al Reported the Contribution Of P-t-butylcalixmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 The negatively charged four carboxylate functions on the top of the deep hydrophobic cavity play a major role in the recognition of charged molecular species. The 1 H NMR titration experiments revealed that host (16) binds with cationic (15, 21, 22) and neutral guests (17)(18)(19)(20) in water, with high binding constants in order of 10 4 -10 5 M -1 .…”
Section: Wwwintechopencommentioning
confidence: 99%